Does microfinancing, financial inclusion, and educational loans alleviate poverty and inequality: evidence from Vietnam - Tran, Trung Kien (Technological and Economic Development of Economy, 2023)
Poverty reduction is considered as the top priority of governments and international institutions. At the same time income inequality is a far-reaching concern especially in emerging nations. US former president even labelled income inequality and poverty are the challenges of our times. Theoretically there are different views on the impact of microfinancing and financial inclusion on income inequality and poverty, hence, it is interesting to evaluate these estimations in Vietnamese context from 1986 to 2020. The researchers have applied the Bayesian Auto-regressive Distributed Lags (BARDL) model and exposed that microfinancing, financial inclusion, educational loans increase income equality and reduces poverty. Based on the evidences, the paper implies that government institutions must focus on microfinancing and financial inclusion aspects to facilitate poor and boost prosperity which ultimately brings income equality.First published online 21 November 2023